The origin of the splitting of 13C and 15N NMR signals of 3(5)-phenyl-5(3)-methylpyrazolium chloride and bromide in the solid state: Quantum Espresso calculations - Alkorta, Ibon (2014)
A combination of 13C and 15N CPMAS NMR spectroscopy and theoretical methods (DFT and DFT-D) was used to discuss the observation of large splittings affecting some atoms in 3(5)-phenyl-5(3)-methylpyrazolium chloride and bromide. Conventional calculations using fully optimized structures with C2 symmetry reproduce solution spectra, but the large splitting observed for the signals of several pyrazolium carbon and nitrogen atoms in the solid-state can only be explained by calculations employing the experimental P21/n geometry and periodic boundary calculations.